2014
DOI: 10.1080/17405629.2014.975790
|View full text |Cite
|
Sign up to set email alerts
|

Associations between risk behaviour and social status in European adolescents

Abstract: Both theory and empirical evidence suggest that adolescents engage in risk behaviour to gain mature status, thereby becoming popular among their peers. Using a cross-sectional design with 20 school classes from higher secondary schools in Austria and the Netherlands, associations between risk behaviour and social status in late adolescence were examined (N ¼ 408, M age ¼ 16.95, SD ¼ 0.81, 50% male). Popularity and likeability were assessed as distinct facets of social status in adolescence using peer nominatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Furthermore, popularity is positively related to sexual activity (Prinstein et al 2003); adolescents who reported engagement in oral sex and sexual intercourse were seen as more popular by their peers than adolescents who did not report any sexual activity. Moreover, it has been shown recently that alcohol use, tobacco use, marijuana use, and sexual intercourse can be explained by a single underlying factor, and that this underlying factor positively predicts popularity (Agan et al 2014). Collectively, these studies indicate that popularity is both an antecedent and a consequence of various risk behaviors.…”
Section: Popularity and Its Behavioral Correlatesmentioning
confidence: 97%
“…Furthermore, popularity is positively related to sexual activity (Prinstein et al 2003); adolescents who reported engagement in oral sex and sexual intercourse were seen as more popular by their peers than adolescents who did not report any sexual activity. Moreover, it has been shown recently that alcohol use, tobacco use, marijuana use, and sexual intercourse can be explained by a single underlying factor, and that this underlying factor positively predicts popularity (Agan et al 2014). Collectively, these studies indicate that popularity is both an antecedent and a consequence of various risk behaviors.…”
Section: Popularity and Its Behavioral Correlatesmentioning
confidence: 97%
“…All these characteristics require children to flexibly respond to social situations, thus being resilient. On the other hand, popularity also is associated with increased levels of aggression (Mayeux et al., ; Schwartz & Hopmeyer Gorman, ) and to risky and impulsive behavior especially in adolescence (e.g., Agan et al., ; Mayeux et al., ; Schwartz & Hopmeyer Gorman, ). Although impulsivity or risky behaviors were not assessed directly, ego undercontrol is indicative of poor impulse inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Still, an interesting paradox remains when trying to explain the association between ego undercontrol and popularity. Based on research one may explain the relationship by impulsivity; ego undercontrol is characterized by high impulsivity (Block & Block, ), and popularity is related to more impulsive behaviors (e.g., Agan et al., ; Mayeux et al., ; Schwartz & Hopmeyer Gorman, ). Thus, children who are more undercontrolled may show more unplanned, impulsive behaviors (both positive and negative), which make them more visible and popular in the peer group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: ausência de conflitos e negligência e existência de afeto positivo); e ao nível da comunidade, são referidos os recursos institucionais e o suporte social. O suporte social na família e na comunidade potenciam a integração dos jovens e a criação de oportunidades de desenvolvimento de habilidades pró-sociais (Agan, Costin, Deutz, Edelsbrunner, Zális, & Franken, 2015;Burfeind & Bartusch, 2011).…”
Section: Delinquência Juvenil: Como Tem Sido Estudadaunclassified